Penatalaksanaan Holistik Pada Laki-Laki Usia 69 Tahun Dengan PPOK Dan Hipertensi Grade II Melalui Pendekatan Kedokteran Keluarga - Rizki Arisandi; Dian Isti Angraini (CV. Jasa Sukses Abadi, 2022)
Changes in the level of welfare of the Indonesian people have led to an increase in the prevalence of non-communicable diseases, one of which is Chronic Obstructive Pulmonary Disease (COPD). The prevalence of COPD in Indonesia is 3.7% and in Lampung the prevalence is 2.04% and ranks number 7 of the 10 most common diseases found in Lampung. In addition, it is estimated that there are 1.28 billion people aged 30-79 years who have hypertension, of which two thirds live in developing countries, and about 46% are not aware of having hypertension. Less than half (42%) of the population with hypertension is diagnosed and treated. In this case report, it is reported that a 69-year-old male patient with COPD and grade II hypertension had concerns that his complaints would increase and not improve. The limited knowledge about the patient's health condition in the form of risk factors, disease prevention, treatment patterns and the lack of motivation and encouragement from the family to stop smoking and take the patient for routine health control are factors that cause problems that occur in patient and family. The management was carried out holistically using a family medicine approach and after evaluation it was found that the patient's symptoms were reduced, increased knowledge, and changes in the patient's diet and physical activity.